PEMBERIAN TABLET ZINC DENGAN DURASI DIARE PADA BALITA - Yuniar Kusumawardani Yuniar Kusumawardani (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2021)
Background : In Indonesia, diarrhea is still the cause of infant mortality. Government Tablet.The benefits of zinc can help the process of improvement in pushing food. Objective : from thisstudy to analyze zinc tablets with the duration of diarrhea in infants. Method : Disable this researchusing Cross-Sectional. The technique used in taking the sample is accidental sampling with a sampleof 75 toddlers. Data is collected by a questionnaire distributed online using the help of Google forms.This study uses the Rank Spearman correlation test. Results : From 75 respondents the averagedelivery of zinc tablets for 6 days and from 75 respondents the average duration of diarrhea inchildren for 3 days. Conclusion : there was a contribution of zinc tablets with a duration of diarrheain infants with p values (0.027). Recommendation : This research suggests more assistance ingiving zinc tablets to be more compliant and can support research results.